Wellness tourism in Southeast Asia : the case study of Six Senses Hotels Resorts & Spas - Silva, Sofia de Sá Barbosa e (2018)
A context of increased demand for wellness tourism is attracting new players in the tourism industry. The concept of wellness tourism has emerged but hasn’t broken through yet: it is already defined and presented in the literature and there is a clear growing demand, however, it is not yet totally clear the players’ strategy, who are still searching how to refine their offerings. The purpose of the present study is to investigate how significant is wellness tourism to today’s consumer needs and how hotels can improve their strategies to better respond to those needs. The study was done with a qualitative case study approach using the Six Senses Hotels Resorts & Spas case and the primary data was collected through a survey and interviews, which were triangulated with secondary data from TripAdvisor. From the results obtained it is evident that, while the categories qualification during a traditional tourism experience and, concretely, a wellness experience can be similar, the prioritization and, itself, the categories value scale that emerge are distinct from each other. Therefore, it is not possible yet to outline the existence of a well-defined gap between wellness tourism concept and the traditional tourism notion. However, with the growing concern for health and the increasing stress levels, the demand for this type of tourism offerings has the tendency to increase. The contribution of this work to Six Senses and other related organizations will be a presentation of possible improvements for the strategy to be implemented, so that they can respond more effectively to consumer needs.